2020
DOI: 10.1002/wsbm.1507
|View full text |Cite
|
Sign up to set email alerts
|

Current applications of mathematical models of the interstitial cells of Cajal in the gastrointestinal tract

Abstract: The interstitial cells of Cajal (ICC) form interconnected networks throughout the gastrointestinal (GI) tract. ICC act as the pacemaker cells that initiate the rhythmic bioelectrical slow waves and intermediary between the GI musculature and nerves, both of which are critical to GI motility. Disruptions to the number of ICC and the integrity of ICC networks have been identified as a key pathophysiological mechanism in a number of clinically challenging GI disorders. The current analyses of ICC generally rely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 122 publications
0
12
0
Order By: Relevance
“…Analyses of ICC network in the gastric tissue have been largely limited to small-scale 2D images and rely on nuclei counts. 20 We presented an approach using the Weka FRF classification to segment networks of ICC and followed by structural analysis of the networks. The reported AUROC of 0.973 for the segmentation of ICC-MP networks, and an AUROC of 0.995 for the segmentation of ICC-IM networks demonstrates accurate and robust performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of ICC network in the gastric tissue have been largely limited to small-scale 2D images and rely on nuclei counts. 20 We presented an approach using the Weka FRF classification to segment networks of ICC and followed by structural analysis of the networks. The reported AUROC of 0.973 for the segmentation of ICC-MP networks, and an AUROC of 0.995 for the segmentation of ICC-IM networks demonstrates accurate and robust performance.…”
Section: Discussionmentioning
confidence: 99%
“…17,25 Multiple histopathological and confocal imaging evidences have demonstrated significant ICC changes associated with various GI motility disorders. 20 In particular, histopathological findings have revealed that dysmotility is strongly associated with reduced ICC numbers. 12 The assessment of ICC at present is limited by the lack of readily available quantitative metrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of mathematical modeling to study other aspects of the stomach, such as neural regulation, biomechanics and luminal flow patterns is relatively new. A number of ICC and smooth muscle cell models have been developed to simulate normal and abnormal function (Lees- Green et al, 2011;Mah et al, 2020). Anatomically realistic models have been developed over which slow wave function can be simulated (Cheng et al, 2007.…”
Section: Future Directions For Modelingmentioning
confidence: 99%
“…In our experiments, we found that the antagonist of Ach M-receptor, nitric oxide synthase inhibitor, or sodium channel blocker could not block the effect of R568 on gastric smooth muscle strips completely, so we speculated that interstitial Cajal cells (ICCs) may also mediate the effect of R568. An ICC is a special type of cell found in the GI tract, mainly including the following types: myenteric ICC (ICC-MY), located between the annular and longitudinal muscularis; deep muscular plexus ICC, located between the annular muscular layers; submucosal ICC, located in the annular muscle layer and submucosa; and intramuscular ICC, located in the annular and longitudinal muscle bundles [25, 26]. ICC-MY are the pacemaker cells of GI slow waves (SWs), which have the functions of generating spontaneous signals and conducting SW potentials, whereas other ICCs have no ability to generate pacing currents, but they transmit signals of neurotransmitters to smooth muscles.…”
Section: Introductionmentioning
confidence: 99%